2000
DOI: 10.1046/j.1365-2826.2000.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Corticosterone Administration Dose‐Dependently Modulates Aβ(1–42)− and NMDA‐Induced Neurodegeneration in Rat Magnocellular Nucleus Basalis

Abstract: The impact of glucocorticoids on beta-amyloid(1-42) (Abeta(1-42)) and NMDA-induced neurodegeneration was investigated in vivo. Abeta(1-42) or NMDA was injected into the cholinergic magnocellular nucleus basalis in adrenalectomized (ADX) rats, ADX rats supplemented with 25%, 100%, 2x100% corticosterone pellets, or sham-ADX controls. Abeta(1-42)- or NMDA-induced damage of cholinergic nucleus basalis neurones was assessed by quantitative acetylcholinesterase histochemistry. Plasma concentrations of corticosterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 59 publications
7
52
0
Order By: Relevance
“…57 Moreover, in vivo chronic corticosterone administration was shown to increase A␤ and N-methyl-D-aspartate-induced neurodegeneration in cholinergic neurons from the nucleus basalis in the rat. 56 In the present study, we obtained clear evidence that A␤ [25][26][27][28][29][30][31][32][33][34][35] increased the blood concentration of corticosterone from the first week and at least up to the third week. Note that plasma corticosterone levels observed in A␤ [25][26][27][28][29][30][31][32][33][34][35] -treated rats were in the same range as observed in chronically stressed rats, 58 which is consistent with the long-term hyperactivity of the hypothalamic-pituitary-adrenal axis.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…57 Moreover, in vivo chronic corticosterone administration was shown to increase A␤ and N-methyl-D-aspartate-induced neurodegeneration in cholinergic neurons from the nucleus basalis in the rat. 56 In the present study, we obtained clear evidence that A␤ [25][26][27][28][29][30][31][32][33][34][35] increased the blood concentration of corticosterone from the first week and at least up to the third week. Note that plasma corticosterone levels observed in A␤ [25][26][27][28][29][30][31][32][33][34][35] -treated rats were in the same range as observed in chronically stressed rats, 58 which is consistent with the long-term hyperactivity of the hypothalamic-pituitary-adrenal axis.…”
Section: Discussionsupporting
confidence: 50%
“…Although no data are available on the effects of A␤ peptide injection on hypothalamic-pituitary-adrenal axis activity, several studies have demonstrated that glucocorticoids modulate APP processing, 55 increase A␤ 1-42 -induced neurodegeneration in basal nuclei of Meynert, 56 and increase A␤ [25][26][27][28][29][30][31][32][33][34][35] toxicity in hippocampus neurons. 57 Moreover, in vivo chronic corticosterone administration was shown to increase A␤ and N-methyl-D-aspartate-induced neurodegeneration in cholinergic neurons from the nucleus basalis in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…16,35 Moreover, animal and cell culture experiments show that low-dose glucocorticoid is neuroprotective whereas high-dose is neurodegenerative. 15,36,37 In a similar but randomized trial using a low-dose dexamethasone protocol (0.15 mg kg À1 per day starting dose with a 10-day tapering course; total exposure: 0.88 mg kg À1 ), 35 ELBW neonates received glucocorticoid and 35 patients received placebo. The hormone-supplemented group showed: (1) facilitated weaning from the ventilator, (2) no significant elevation in blood glucose or blood pressure and (3) reduced postnatal weight gain (50% lower than the control group).…”
Section: Postnatal Betamethasone Vs Dexamethasone M Decastro Et Almentioning
confidence: 99%
“…[12][13][14] Animal and tissue culture experiments show that low doses of glucocorticoids are neuroprotective whereas higher doses are neurodegenerative. 13,15 At least 11 systemic reviews on postnatal systemic glucocorticoids published between 1992 and 2001 showed a greater risk of cerebral palsy among premature infants treated with dexamethasone, for long duration (21 to 42 days) using a high dose (>0.5 mg kg À1 per day). 7 Surprisingly, betamethasone is not commonly used as a postnatal glucocorticoid to treat BPD in premature infants even though there is compelling evidence of its safety and efficacy in postnatal outcomes following antenatal betamethasone use during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus appears to be particularly vulnerable to these neurotoxic effects, with CA3 pyramidal neurons being particularly more sensitive compared to CA1 pyramidal cells (Levy et al, 1994). Moreover, combination of differential GC levels with various noxious stimuli [Aβ-toxicity, hypoxia, N-methyl-Daspartate (NMDA)-induced excitotoxicity] leads to either an exacerbation of the neurodegenerative effects (when levels of GCs too low or too high) or an attenuation of the latter (under moderate corticosteroid levels) in a GC concentration-dependent manner (Abrahám et al, 2000). This latter effect has been also observed in animal models of cerebral ischemia, where chronic stress prior of neurovascular pathology was shown to increase stroke vulnerability, likely through GC-related endothelial dysfunction, since this effect was reversed by a GR antagonist (mifepristone) (Balkaya et al, 2011).…”
Section: Neurotoxicity Versus Neuroprotectionmentioning
confidence: 99%